Universal Free School Breakfast: A Qualitative Model for Breakfast Behaviors - Harvey-Golding, Louise; Donkin, Lynn Margaret; Blackledge, John; Defeyter, Margaret Anne (Frontiers in Public Health, 2015)
In recent years, the provision of school breakfast has increased significantly in the UK. However, research examining the effectiveness of school breakfast is still within relative stages of infancy, and findings to date have been rather mixed. Moreover, previous evaluations of school breakfast schemes have been predominantly quantitative in their methodologies. Currently, there are few qualitative studies examining the subjective perceptions and experiences of stakeholders, and thereby an absence of knowledge regarding the sociocultural impacts of school breakfast. The purpose of this study was to investigate the beliefs, views and attitudes, and breakfast consumption behaviors, among key stakeholders, served by a council-wide universal free school breakfast initiative, within the North West of England, UK. A sample of children, parents, and school staff were recruited from three primary schools, participating in the universal free school breakfast scheme, to partake in semi-structured interviews and small focus groups. A Grounded Theory analysis of the data collected identified a theoretical model of breakfast behaviors, underpinned by the subjective perceptions and experiences of these key stakeholders. The model comprises of three domains relating to breakfast behaviors, and the internal and external factors that are perceived to influence breakfast behaviors, among children, parents, and school staff. Findings were validated using triangulation methods, member checks, and inter-rater reliability measures. In presenting this theoretically grounded model for breakfast behaviors, this paper provides a unique qualitative insight into the breakfast consumption behaviors and barriers to breakfast consumption, within a socioeconomically deprived community, participating in a universal free school breakfast intervention program.